An Analysis of Jordan’s Adherence to the NCTM Standards for First Grade Reformed Mathematics Textbooks - Rababah, Ebtesam; Miqdadi , Ruba (Jordan Journal of Educational Sciences, 2017)
This study investigated the compliance of Jordan’s reformed mathematics textbooks for first-graders to the National Council of Teachers of Mathematics’ (NCTM, 2000) standards. The population and the sample of the study consisted of the reformed mathematics textbooks for first-graders in Jordan. An analysis instrument was designed. The validity and reliability of the instrument were ensured. The reformed 2015 mathematics textbook was analyzed with this instrument. The results of the study revealed that the reformed mathematics textbook complied with (31) indicators of (NCTM) standards resulting in a compliance rate of 68%. However, the content did not achieve (14) indicators in the five areas of the content standards. Also, the reformed mathematics textbooks neglected the data analysis and probability standard. The study recommends the following in light of the results: conduct further studies on each grade from kindergarten through twelfth grade, analyzing both the content and process standards of the curriculum